Update on fixation of rigid and foldable posterior chamber intraocular lenses, part II: choosing the correct haptic fixation and intraocular lens design to help eradicate posterior capsule opacification - Ram, Jagat; Apple, David J.; Peng, Qun; Visessook, Nithi; Auffarth, Gerd U.; Schoderbek, Robert J.; Ready, Edgar L. (Ophthalmology, 2003)
Posterior capsule opacification (PCO) is one of the most common complications of cataract surgery, and there is an urgent need to reduce its incidence…
Presented in part at the annual meeting of the Oxford Ophthalmological Congress, Oxford, England, July 1997
Available online 29 July 2003
Gesehen am 26.02.2021